Sources and Number of Coupons for Cigarettes and Snus Received by a Cohort of Young Adults. Issue 1 (January 2018) - Choi, Kelvin; Taylor, Naomi; Forster, Jean
Purpose: To examine the sources of tobacco coupons and their influence on susceptibility to snus use. Design: Cohort study. Setting: Minnesota Adolescent Community Cohort Study. Subjects: A population-based sample of US Midwest young adults in 2011 to 2012 and 2012 to 2013 (aged 22-28; n = 2384). Measures: Exposure to coupons for various tobacco products through various sources in the past 6 months, susceptibility to snus use. Analysis: Multiple logistic regressions. Results: During the 6 months prior to 2012 to 2013 survey, 11% of the sample received coupons for cigarettes, 5% received coupons for snus, 3% received coupons for other smokeless tobacco products, and <1% received coupons for little cigars. Direct mail was the most commonly cited source of cigarette and snus coupons. Tobacco product packaging provided the highest number of tobacco coupons for current and former smokers. Participants without a 4-year college education (compared to those who had a 4-year college education) were more likely to have received coupons for cigarettes and snus and received more coupons for both products ( P < .05). Racial/ethnic minority young adults (vs non-Hispanic white) received more cigarette and snus coupons ( P < .05). Receiving snus coupons was positively associated with susceptibility to snus use ( P < .05). Conclusion: Tobacco companies are successful in reaching young adults using coupons for various tobacco products. Snus coupons may influence snus use, similar to how cigarette coupons influence smoking.